Development of Learning for Tour Guide using Peer-assisted Activities to Increase Achievement - เรียงหา อัญชลี; วุฒิยา กัญญาพัชร; โตสัจจะวงษ์ จรูญวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purpose of this research was to study the Development of learning for tour guide using peer-assisted activities to increase achievement. The sample group was 16 students who are study in tourism for level 3 in semester 1/2024 was elected from purposive sampling and experimental Research . The research instruments were: 1) lesson plans on Thai tourist attractions related to tour guides, 2) a 40-item with 4 multiple choice and 20 points learning achievement test using before and after the intervention. The statistics for data analysis were percentage, mean and standard deviation. The results of the research revealed that: before the intervention, the mean score was 9.87, or 49.38 percent, while after the intervention, their mean score was 15.25, or 76.15 percent. These results suggested that the students post-intervention mean score was higher than that before the intervention, indicating learning progress ranging from 2 to 11 points representing a percentage increase of 10.00-55.00 percent.